GAMBARAN RESPON STRESS HOSPITALISASI PADA ANAK USIA 2 – 3 TAHUNDI RSU Dr. WAHIDIN SUDIRO HUSODO KOTA MOJOKERTO - Lestari, Indah; Ayu Lestari, Dwi (JURNAL KEPERAWATAN BINA SEHAT, 2015)
Hospitalization is a process that is for a reason that is planned or emergency, requiring the child to stay in the hospital, establish treatment and care until their return back home. The reaction of children to hospitalization is the child will lose control function, with the loss of control functions with respect to motor function. The purpose of this study was to determine how the image of the stress response of children aged 2-3 years when undergoing hospitalization. In a study using descriptive methods. The study population was all pediatric patients treated in RSU Dr. Kertawijaya Wahidin Sudiro Husodo Mojokerto amounted to 20 children. These samples included 20 children taken using consecutive sampling. Data sources using primary data, as data collection using observation techniques and instruments using observation sheet. Data analysis techniques using frequency distribution. The result showed on the first day of hospitalization stress response in children more at this stage of protest and despair that is each numbered nine children, while that to the extent there are only two children refused. On the second day there is a decrease in the stage protests to 4 children, while the stage remains desperate 9 children and at the stage of refusing to rise to 7 children. On the third day decline again on stage protests to 2 chldren, while the stage remains desperate 9 children and at the stage of refusing to rise to 9 anak.Responden average research experience changes the stress response on the first day of hospitalization, second and third. The response of hospitalization of children are influenced by age, gender and experience in the hospital.Keywords: 2-3 Years Childhood, Hospitalization, Stress Response